Empowering educators: exploring the link between teacher leadership and self-efficacy at Chongqing Preschool Education College - Tan, Wenyue; Abdul Aziz, Nor Azni (Human Resource Management Academic Research Society, 2024)
Education is commonly acknowledged as the first stage in the traditional activities carried out by persons in the age of globalization and rapid advancement. The notion being discussed is of utmost importance in enhancing individuals' human capital and is closely connected to their overall well-being and prospects for enhanced quality of life. The objective of this study is to examine the relationship between teacher leadership and teacher self-efficacy among educators at Chongqing Preschool Education College. The study utilized quantitative research methodology, employing the Teacher Effectiveness Scale and the Teacher Leadership Scale to assess these concepts. 200 teachers completed the survey questions. The survey findings indicated that the level of teacher leadership at the school was moderate, while teacher self-efficacy was rather low. Additionally, a robust positive link between the two variables was seen, with a correlation coefficient of .77. The study is significant because it explores the connection between teacher leadership and teacher self-efficacy in the classroom. It also provides useful suggestions for improving the quality of higher education.